Synthesis of Hydrophilic Derivative Surfactants From Algae-Derived Unsaponifiable Lipids - Fioroni, Gina; Katahira, Rui; Van Wychen, Stefanie; Rowland, Steven M.; Christensen, Earl D.; Dong, Tao; Pienkos, Philip T.; Laurens, Lieve M. L. (Frontiers in Chemical Engineering, 2022)
In the context of decarbonizing the economy, the utilization of biologically sourced feedstocks to produce replacements for petroleum-derived materials is becoming more urgent. Improving renewable biomass production and utilization is imperative for commercializing future biorefineries. Algae-derived biomass is a particularly promising feedstock thanks to its attractive oil content and composition; specifically, the high-value products in the unsaponifiable lipids have not been included in a conversion process. Here we demonstrate surfactant synthesis from a complex oil fraction as the hydrophobic donor moieties, yielding products that are similar to commercially available surfactants such as the linear alkyl benzene sulfonates. Unsaponifiable lipids extracted from algae were derivatized to non-ionic surfactants using a green chemical synthesis route based on a double esterification with succinic acid and polyethylene glycol. The in-depth molecular and structural surfactant characterization is included and indicates that the resulting properties fall between those of pure cholesterol and phytol used as surrogates for the reaction synthesis demonstration. This is the first demonstration of an effective and potentially high-value synthesis of functional surfactants with properties that can be tailored based on the relative composition of the resulting hydrocarbon alcohol components in the mixture. This novel green chemistry synthesis approach provides a route to high-value product synthesis from algae.